PEMANFAATAN PATI SAGU DAN TEPUNG BIJI SAGA DALAM PEMBUATAN MI INSTAN - Mukhti Ramadhan; Faizah Hamzah; Rahmayuni ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This study was aimed to evaluate the quality of instant noodles from sago starch by the addition of saga seed flour, which meet the instant noddles quality (SNI 01-3551-2000). Research conducted by experiments using a Completely Randomized Design (CRD) with 6 treatment and 3 replications. The treatment consist of SG0 (noodles from sago starch 100%), SG1 (noodles from sago starch 95%, saga seed flour 5%), SG2 (noodles from sago starch 90%, saga seed flour 10%), SG3 (noodles from sago starch 85%, saga seed flour 15%), SG4 (noodles from sago starch 80%, saga seed flour 20%), SG5 (noodles from sago starch 75%, saga seed flour 25%). The data obtainedwere statistically analyzed using ANOVA. Parameters measuredwere moisture, ash, protein contents and acid value, rehydration time and intactness. The results showed that the ratio of sago starch and saga seed flour significantly on moistureand protein contents, acid value, intactness and rehydration time. The best treatment in this study was 75% sago starch and 25% saga seed flour, with moisture content before frying 5,15%, water content after frying 3,64%, protein content 4,87%, acid value 0,05 ml KOH/g, intactness 95,63% and rehydration time 4,11 minute. Instan noodles produced from sago starch and saga seed flour are meet the quality standard of instant noodles (SNI-01-3551-2000) except SG0 treatment. Keywords: Sago starch, saga seed flour, instant noodles